Sosialisasi Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga Di Desa Bitefa Kecamatan Miomaffo Timur Kabupaten Timor Tengah Utara - Sepriliani Suryati Elin Satung; Maria; Ferdinandus Bani; Benediktus Peter Lay; Teresia Din; Filemon Fridolino Ngebos (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Domestic Violence (DV) remains a serious human rights violation in Indonesia, particularly in rural areas with limited access to legal services and victim protection. East Nusa Tenggara Province, including Timor Tengah Utara Regency, continues to record high incidences of domestic violence influenced by patriarchal culture, low legal awareness, and the predominance of customary-based settlements that often disadvantage victims. This community service program aims to enhance legal awareness and understanding among the residents of Bitefa Village, Miomaffo Timur District, Timor Tengah Utara Regency, regarding Law Number 23 of 2004 on the Elimination of Domestic Violence as a preventive and responsive legal framework. The activity employed a legal counseling method through structured presentations, interactive discussions, and evaluation using pre-test and post-test instruments. The program was conducted on September 23, 2025, involving 25 participants consisting of village officials, hamlet heads, and community members. The materials delivered covered the definition of domestic violence, its various forms, legal protection mechanisms for victims, criminal sanctions for perpetrators, as well as the roles of the state and the community in preventing and addressing domestic violence. The results indicate a significant improvement in participants’ understanding of domestic violence and the legal protections available to victims after the counseling session. The discussion sessions revealed a shift in community perspectives, particularly regarding the relationship between customary law and state law in handling domestic violence cases. This program is expected to contribute to the prevention of domestic violence and to support the creation of a safe, harmonious, and gender-just household environment in Bitefa Village, in line with the National Action Plan on the Elimination of Domestic Violence